Anticancer Immunomodulatory Activity of Male Papaya Leaf Extract (Carica papaya L.) Through PD-1/PD-L1 Pathway Modulation: An In Silico and In Vitro Study - Lisa Savitri; Kharisul Ihsan; Elfred Rinaldo Kasimo; Rochmad Krissanjaya (Sunan Kalijaga State Islamic University & Society for Indonesian Biodiversity, 2026)
Cancer immunotherapy targeting the programmed death-1/programmed death-ligand 1 (PD-1/PD-L1) pathway has shown remarkable clinical success; however, high costs and immune-related adverse effects remain major challenges. Natural products with immunomodulatory properties offer a promising alternative approach. Male papaya leaves (Carica papaya L.) are traditionally used in herbal medicine, yet their potential role in immune checkpoint modulation remains largely unexplored. This study aimed to investigate the anticancer immunomodulatory activity of male papaya leaf extract through PD-1/PD-L1 pathway modulation using integrated in silico and in vitro approaches. Molecular docking analysis was performed to evaluate the interaction between major phytochemical compounds and PD-1/PD-L1 proteins. In vitro cytotoxic activity was assessed using the MTT assay on cancer cell lines, while immunomodulatory effects were evaluated by measuring interferon-gamma (IFN-gamma) and interleukin-2 (IL-2) levels using ELISA. PD-L1 protein expression in treated cancer cells was analyzed by Western blotting. The docking results demonstrated strong binding affinities of flavonoid compounds, particularly quercetin, toward PD-L1, involving key residues at the active binding site. The extract exhibited dose-dependent cytotoxic effects with moderate IC50 values. Treatment with male papaya leaf extract significantly increased IFN-gamma and IL-2 secretion in immune cells and markedly downregulated PD-L1 protein expression in cancer cells. In conclusion, male papaya leaf extract exhibits promising anticancer immunomodulatory activity by modulating the PD-1/PD-L1 immune checkpoint pathway. These findings highlight the potential of male papaya leaves as a natural source of immune checkpoint modulators and support further investigation for their development as complementary agents in cancer immunotherapy.